Troubleshooting Microsoft Teams : enlisting the right approach and tools in teams for mapping and troubleshooting issues - Ilag, Balu N.; Sabale, Arun M (Apress, 2022)
Learn and understand Microsoft Teams functionality, potential issues, and the tools available to troubleshoot Teams. This book provides a complete overview of Teams Phone system (PSTN) connectivity, call routing and quality troubleshooting, and best practices to support a Teams environment. The book begins with an introduction to Microsoft Teams and it provides a troubleshooting terminology. You will understand how to identify and develop a systematic approach for troubleshooting Teams. You will learn Teams Phone (voice) management and how to handle issues related to: Direct Routing connectivity, call routing, emergency calling, and much more. The book covers issues related to Teams client-side and external access along with Teams call quality troubleshooting. You will gain knowledge of real-world issues and use Teams troubleshooting tools such as the: Connectivity Analyzer, call diagnostic tool, SBC Syslog, Call Quality Dashboard, and quality analytics tool. You will go through the: Call Quality Dashboard with custom queries, PowerBI connector tool for the Teams Call Quality Dashboard, Teams Phone system Direct Routing Health Dashboard for call quality troubleshooting, and learn how to design PowerBI-based Teams reports. After reading this book, you will be able to quickly diagnose Teams connectivity and quality problems, and discover the root cause of any Teams issue. This book also is a practical guide you can use to prepare for the certification exam on troubleshooting Microsoft Teams (Exam MS-740).